ANALYSIS OF THE INFLUENCE OF AUCTION SERVICE QUALITY ON SERVICE USER SATISFACTION AT THE YOGYAKARTA STATE WEALTH AND AUCTION SERVICE OFFICE (KPKNL) YOGYAKARTA - Erwin Hanggoro Agung Nugroho; Muinah Fadhilah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine how much influence the quality of auction services has on service user satisfaction at the Yogyakarta KPKNL. The independent variable in this study is the quality of auction services, which includes 5 (five) dimensions namely reliability, assurance, physicality, empathy and responsiveness. While the dependent variable is service user satisfaction as measured using the appropriate measurement scale. The research method used was a survey using a questionnaire as a data collection instrument. The data obtained was analyzed using the Service Customer Satisfaction Index/CSI technique to determine the level of satisfaction of service users as a whole by taking into account the level of importance of the product or service attributes and obtaining the result that the service element in the perspective of the level of importance and satisfaction resulted in a total CSI of 187.9 or with the criteria is Very Satisfied.